Empowering Women Through Sustainable Development: Strategies for Female SMEs in Siak Regency - Wasnury, Rendra; Indarti, Sri; Marpaung, Rio; Novrianti, Dian Puspita (Journal of Ecohumanism, 2025)
The empowerment of female-owned SMEs (Small and Medium Enterprises) in Siak Regency plays a pivotal role in driving family economic welfare and contributing to sustainable development. Despite various government policies and programs implemented by local agencies, significant challenges persist, including limited access to capital, low financial literacy, and minimal utilization of digital marketing technologies. This study analyzes the progression of female SME empowerment, identifies strengths, weaknesses, opportunities, and threats (SWOT analysis), and formulates effective strategies. The findings highlight the need for targeted training, enhanced financial access, and strategic partnerships with public and private sectors. By fostering gender equality and adopting environmentally friendly practices, the study provides actionable recommendations for inclusive and sustainable economic development in Siak Regency.